Isoniazid, Rifampin, and Pyrazinamide Plasma Concentrations in Relation to Treatment Response in Indonesian Pulmonary Tuberculosis Patients - Burhan, Erlina (American Society for Microbiology, 2013)
Numerous studies have reported low concentrations of antituberculosis drugs in tuberculosis (TB) patients, but few studies have examined whether low drug concentrations affect TB treatment response. We examined steady-state plasma concentrations of isoniazid, rifampin, and pyrazinamide at 2 h after the administration of drugs (C(2 h)) among 181 patients with pulmonary tuberculosis in Indonesia and related these to bacteriological response during treatment. C(2 h) values below reference values for either isoniazid, rifampin, or pyrazinamide were found in 91% of patients; 60% had at least two low C(2 h) concentrations. The isoniazid C(2 h) was noticeably lower in fast versus slow acetylators (0.9 mg/liter versus 2.2 mg/liter, P < 0.001). At the end of treatment, 82% of the patients were cured, whereas 30 patients (17%) had dropped out during the study, and 2 patients (1%) failed treatment. No association was found between C(2 h) concentrations and sputum culture results at 8 weeks of treatment. Post hoc analysis showed that patients with low pyrazinamide C(2 h) (P = 0.01) and patients with large extensive lung lesions (P = 0.01) were at risk of at least one positive culture at week 4, 8, or 24/32. Antituberculosis drug concentrations were often low, but treatment response was nevertheless good. No association was found between drug concentrations and 8 weeks culture conversion, but low pyrazinamide drug concentrations may be associated with a less favorable bacteriological response. The use of higher doses of pyrazinamide may warrant further investigation.